The Role of Macrophages During Mammalian Tissue Remodeling and Regeneration Under Infectious and Non-Infectious Conditions - Bohaud, Candice; Johansen, Matt D.; Jorgensen, Christian; Kremer, Laurent; Ipseiz, Natacha; Djouad, Farida (Frontiers in Immunology, 2021)
Several infectious pathologies in humans, such as tuberculosis or SARS-CoV-2, are responsible for tissue or lung damage, requiring regeneration. The regenerative capacity of adult mammals is limited to few organs. Critical injuries of non-regenerative organs trigger a repair process that leads to a definitive architectural and functional disruption, while superficial wounds result in scar formation. Tissue lesions in mammals, commonly studied under non-infectious conditions, trigger cell death at the site of the injury, as well as the production of danger signals favouring the massive recruitment of immune cells, particularly macrophages. Macrophages are also of paramount importance in infected injuries, characterized by the presence of pathogenic microorganisms, where they must respond to both infection and tissue damage. In this review, we compare the processes implicated in the tissue repair of non-infected versus infected injuries of two organs, the skeletal muscles and the lungs, focusing on the primary role of macrophages. We discuss also the negative impact of infection on the macrophage responses and the possible routes of investigation for new regenerative therapies to improve the recovery state as seen with COVID-19 patients.